Zinc toxicity and sequential extraction in water and sediments of tropical lake: A case study of Ahémé Lake in Benin - Chouti, Waris (My University, 2017)
The presence of trace metals in surface water at concentrations above natural standards becomes a situation of increasing concern. Lake Ahémé, the second lake in Southern Benin with an area of floods with a maximum depth of 2.35m did not remain on the fringe of this crucial situation. In fact, over half a century, we witness poor management of this ecosystem through activities that ensure little its situation, water and sediment sampling work was carried out on four stations to characterize the chemical standpoint Lake Aheme-Guezin. In order to better characterize the pollution degree of the ecosyst risk of toxicity in the water by the seeding method of Onion roots. Meanwhile, a study on the chemical speciation of zinc in sediment was carried out by the sequential extraction method of Tessier. Data processing was performed by Microsoft Office Excel 2013; the collection card has been completed and digitized through the Google Earth and Arc software. Geographic coordinates were determined through Geodata conversion software. The toxicity tests results indicat a high toxicity degree in water and those of speciation gives much higher concentration standards on all the sampling points. These results show that human activities around the lake and within the complex asphyxiated by toxic metals from household waste with waste water (domestic and valves).
Keywords: Speciation; lake sediment; sequential extraction; zinc toxicity; Guezin